2014
DOI: 10.1007/s10802-014-9915-4
|View full text |Cite
|
Sign up to set email alerts
|

Re-visiting Internet Addiction among Taiwanese Students: A Cross-Sectional Comparison of Students’ Expectations, Online Gaming, and Online Social Interaction

Abstract: Using expectancy theory, this study aimed at identifying the attitudinal/behavioral factors that explain the relationship between Internet expectancies and Internet addiction among Taiwanese adolescents. A total of 25,573 students (49.8% boys and 50.2% girls) across junior and senior high schools participated in the study. The students reported on their background characteristics, general expectations from the Internet, attitudes toward online social interaction and online gaming, preferences in online social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 57 publications
5
30
1
1
Order By: Relevance
“…Finally, in line with the data reported in the previous research (Griffiths, Davies, & Chappell, 2003; Ko, Yen, Chen, Chen, & Yen, 2005; Lee, Ko, & Chou, 2015), gender and age differences were found. More specifically, males and young adults seemed to be more engaged in gaming activities.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, in line with the data reported in the previous research (Griffiths, Davies, & Chappell, 2003; Ko, Yen, Chen, Chen, & Yen, 2005; Lee, Ko, & Chou, 2015), gender and age differences were found. More specifically, males and young adults seemed to be more engaged in gaming activities.…”
Section: Discussionsupporting
confidence: 91%
“…The study also showed that dysfunctional coping style and Internet-use expectancies are significant predictors of ICD, which is consistent with other studies about predictors of Internet addiction (Tonioni et al, 2012; Turel and Serenko, 2012; Xu et al, 2012; Tang et al, 2013; Brand et al, 2014a; Kardefelt-Winther, 2014; Lee et al, 2015). Individuals with high expectancies toward the Internet as helpful tool to distract from annoying duties or to experience pleasure as well as with dysfunctional coping strategies such as denial or behavioral disengagement have a higher risk to develop an ICD.…”
Section: Discussionsupporting
confidence: 90%
“…Gender is one such factor and is also something which can be relatively easily used as the basis for personalisation and customisation. Research into child and adolescent populations suggests that there are gender differences in the pathways for the development of DA, with boys being more likely to experience DA through online video gaming than girls, as well as being more likely to use the internet excessively to attempt to develop new friendships [8]. Gender has also been found to be an important factor in other behavioural domains that may relate to DA.…”
Section: Introductionmentioning
confidence: 99%